Trichoderma reesei (Hypocrea jecorina) Bgl1 is a Novel, Exo-Acting Glucanase and Xylanase - Brumm, Phillip; Xie, Dan; Allen, Larry; A. Mead, David (Journal of Enzymes, 2019)
Trichoderma reeseiβ-glucosidase (Bgl1) is one of four enzymes demonstrated to act synergistically to degrade cellulose both in vitro and in vivo. Our work attempted to better understand the substrate specificity and potential biotechnological applications of Bgl1. T. reesei Bgl1H cleaves over 80% of the β-(1-4) and β-(1-3) linkages in β-glucan and 14% of the β-(1-4) linkages in amorphous cellulose, significantly more than any tested bacterial β-glucosidase. Bgl1H cleaves 50% of the β-(1-4) linkages in xyloglucan when supplemented with cellulase and α-xyloside. Approximately 20% conversion to glucose was obtained from insoluble β-(1,3)-linked curdlan using only Bgl1H; addition of a curdlanase resulted in conversion of approximately 70% of the curdlan to glucose. Bgl1H also produces xylose from xylooligosaccharides and debranched xylans. For both glucans and xylans, the relative rates of hydrolysis increase with increasing polysaccharide chain lengths. Bgl1H is able to partially degrade β-glucan in a variety of grain components; addition of endo-acting enzymes improved the enzyme’s performance on these grain components. The ability of this enzyme to produce monosaccharides from undigestible polysaccharides suggest it may have potential in improving utilization of carbohydrates in animal feed, fermentations, and other biotechnological applications.
Keywords: Trichoderma reesei; Hypocrea jecorina; Glucanase; Xylanase; Cellulose